UPAYA MENINGKATKAN MINAT DAN PRESTASI BELAJAR MATEMATIKA DENGAN METODE JOYFUL LEARNING PADA SISWA KELAS VIIG SMP NEGERI 2 SANDEN TAHUN PELAJARAN 2012/2013 - Fisa Bil Huro; Benedictus Kusmanto (Universitas Sarjanawiyata Tamansiswa, 2015)
The research purposes to increases interest and mathematics achievement with Joyful Learning method in class VII G SMP Negeri 2 Sanden. The research subjects were students of class VII G SMP Negeri 2 Sanden and object of this research were interests and mathematics achievement. The results showed that interest and mathematics achievement increase. The results can be seen from questionnaire data pre-term by 62.88% with moderate category, increased to 69.16% with the moderate category in first term. Then increased again to 78.01% in second term with the high category. The results of mathematics achievement obtained from test, with percentage completeness obtained pre-term 16.67% with an average of 56.07. In first term increased to 63.33% with an average of 69.02 and in second term increased to 80% with average value of 80.67.